Expatriate Compensation and its Impact on Employee Satisfaction: A Single Case Study from a Finnish Multinational Company - Skomars, Denise (My University, 2020)
Expatriate management is a well-researched area in international human resource manage-ment. The focus on expatriates has previously lied on cross-cultural adjustment when discussing the success or failure of an international assignment. However, expatriate compensation is an equally essential part when disclosing a successful international assignment. Therefore, it cre-ates a need to explore the link between expatriate compensation and the impact it has on em-ployee satisfaction amongst international assignees. The aim of this research is to understand the compensation package and the differences in ap-proaches that are offered by multinational companies, and how the employee satisfaction is influenced by the compensation package. The objectives of this study are to explore how finan-cial and non-financial values affect the employee’s satisfaction when it comes to compensation and to identify key factors in the compensation package that are essential for the international assignment. The theoretical overview consists of international assignments, expatriate compen-sation approaches and lastly employee satisfaction. The thesis is conducted as a single case study from a Finnish multinational company, and the data has been collected using semi-struc-tured interviews with the key informants who has either been on a long-term or short-term international assignment. Additionally, an interview with a key informant at the HR of the case company has been conducted. In this study, the research question “how is the employee satis-faction of international assignees affected by their compensation package?” has been answered. The findings of this thesis present that the assignees’ primary motive for accepting an interna-tional assignment was their internal motivation for career development and experience, and therefore they did not expect nor demanded a generous renumeration package. However, the key components of the compensation were insurance, taxation consultation, adequate housing and social security. Furthermore, it was the feeling of being taken care of by the company that was the essential part. The compensation approach solely did not equal employee satisfaction, but in combination with their values, employee satisfaction could be met. The findings also show that meeting the expectations of an expatriate is the most difficult aspect of designing a compensation package for the assignee, and therefore there need to be clear communication from the initial start of the expatriation process.
Keywords: expatriates; pay policy; compensation (activity); human resource management; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business